Modified Slide Deck in Teaching Filipino and Its Effect to Grade 7 Student’s Learning - ZAMORA, PEERLESS QUEEN (International Journal of Arts, Sciences and Education, 2025)
The continuous advancement of technology underscores the importance of modern instructional tools in enhancing student learning. This study aims to examines the effectiveness of Modified Slide Decks as a teaching aid in the Grade 7 Filipino learners. The primary research problem focuses on assessing the impact of this tool on students’ academic performance. Using a quasi-experimental research design, the study was conducted at New Panay National High School, Esperanza, Sultan Kudarat, involving forty-seven learners purposively selected students with low Phil-IRI scores during the pre-test examination. Data analysis employed mean, standard deviation, and t-test to measure the effect of Modified Slide Decks on student learning. Findings revealed a significant improvement in students’ learning outcomes after integrating Modified Slide Decks into instruction. Pre-test scores showed low performance, while post-test results demonstrated higher achievement, confirming the tool’s effectiveness in enhancing learning. Based on these results, the study recommends the continued and expanded use of Modified Slide Decks in Filipino instruction. Additionally, teacher training, seminars, and workshops should be conducted to enhance educators’ ability to develop and utilize innovative instructional materials. Continuous monitoring and evaluation are essential to refine the tool and optimize learning outcomes. The significance of this study lies in its contribution to technology-driven instruction, demonstrating that digital teaching aids can improve student performance. Future research should explore the applicability of Modified Slide Decks in different subjects and learning levels to establish its broader impact on education. Keywords: Teknolohiya, Integrasyon, Pagkatuto. Modified Slide Deck, Pagtuturo sa Filipino